PARADIGMATIC FRAMEWORK OF DEMOCRATIC AND HUMANIST ISLAMIC EDUCATION - Sri Haryanto (Jurnal Mantik, 2022)
This research is qualitative research that aims to find and find how the paradigmatic framework of Islamic education is democratic and humanistic, research information is sourced from literature. Amid globalization, Islamic education is not only required to be able to print the younger generation of the nation who have reliable intellectual intelligence but Islamic education is also expected to print generations who are emotionally intelligent, spiritual and graceful in morals. Therefore, Islamic education should not only be oriented toward the "transfer of knowledge”, but Islamic education must also be oriented toward the awareness and implementation of knowledge in living the lives and lives of students in their social environments. The rapid development of science and technology in the last decade also requires Islamic education to change its paradigm. From paradigms oriented to the past (medieval) to paradigms oriented to the future, from paradigms that preserve progress, to paradigms that pioneer progress, and from paradigms that are feudal to democratic and humanistic paradigms. The essence of the paradigm of democratic and humanistic Islamic education is education in which there is a dialogical atmosphere, tolerance, mutual respect, and respect for freedom of opinion, freedom to express ideas, provide space for the active involvement of learners in various activities in schools and community life. Education is oriented towards the development of all aspects and potentials that humans have as a whole and integral.